Penyelesaian Masalah Matematika Pada Tipe Kepribadian Phlegmatis - Rina Agustina (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2014)
The research was a descriptive qualitative. The prosedure of selecting the subjects used purposive sampling. The data of the research was collected by using think aloud method. The validity of the data used was triangulation. The results of the research showed that problem solving of personality type phlegmatic: (a) understanding the information  by looking at the questions, then making a picture, had no difficulty in turning information into mathematical form and looking back at the questions to find the things in questions, (b) solving the problems by planning a solution that is started from the specified requirements in the matter, experiencing difficulty to change the equation initial information to be used in the calculation, and was not able to find the other formula which was different from the derivative function; (c)  convincing the answer by looking back at the existing calculation, adjusting the obtained solution that was based on actual event and re-adjusting it to the problem in question